2023
DOI: 10.1128/jcm.01581-22
|View full text |Cite
|
Sign up to set email alerts
|

Review of Clinical and Laboratory Diagnostics for Coccidioidomycosis

Abstract: Coccidioidomycosis is a fungal disease associated with soil exposure that frequently goes undiagnosed due at least in part to its nonspecific presentation and the lack of clinical suspicion by health care providers. Currently available diagnostics for coccidioidomycosis offer qualitative results that can suffer from low specificity, while semiquantitative assays are labor-intensive and complex and can require multiple days to complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Most of the coccidioidomycosis cases are diagnosed using Ab detection assays, based on complement fixation (CF), gel precipitation tests (CIE and ID), and EIA. The main limitation of these assays is the need for highly trained laboratorians, special laboratory instruments, and prolonged turnaround time for results [19]. LFA technology has significantly improved this limitation; these assays are simple, accurate, and rapid.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the coccidioidomycosis cases are diagnosed using Ab detection assays, based on complement fixation (CF), gel precipitation tests (CIE and ID), and EIA. The main limitation of these assays is the need for highly trained laboratorians, special laboratory instruments, and prolonged turnaround time for results [19]. LFA technology has significantly improved this limitation; these assays are simple, accurate, and rapid.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Irinyl et al showed the utility of MinION-based NGS for the diagnosis of Pneumocystis jirovecii directly from respiratory (sputum and BAL) samples [ 81 ]. NGS also helps in differentiating fungal species; for example, Coccidioides immitis and Coccidioides posadasii can be differentiated, which otherwise are difficult to identify with available conventional techniques [ 82 ].…”
Section: Other Emerging Modalities Of Nucleic-acid-based Molecular Di...mentioning
confidence: 99%
“…Diagnostics for coccidioidomycosis have recently been thoroughly reviewed in [71]. Culture or isolation of Coccidioides spp.…”
Section: Diagnosismentioning
confidence: 99%